The vibrationally mediated photodissociation of Cl2. - Campbell, E; Alekseyev, AB; Balint-Kurti, G; Brouard, M; Brown, A; Buenker, R; Johnsen, A; Kokh, D; Lucas, S; Winter, B (2012)
The photodissociation of vibrationally excited Cl(2)(v = 1) has been investigated experimentally using the velocity mapped ion imaging technique. The experimental measurements presented here are compared with the results of time-dependent wavepacket calculations performed on a set of ab initio potential energy curves. The high level calculations allow prediction of all the dynamical information regarding the dissociation, including electronic polarization effects. Using a combination of theory and experiment it was found that there was negligible cooling of the vibrational degree of freedom of the parent molecule in the molecular beam. The results presented are compared with those following the photodissociation of Cl(2)(v = 0). Although the same electronic states are found to be important for Cl(2)(v = 1) as for Cl(2)(v = 0), significant differences were found regarding many of the observables. The overall level of agreement between theory and experiment was found to be reasonable and confirms previous assignments of the photodissociation mechanism.